PENGARUH KOMPETENSI DAN MOTIVASI KERJA GURU TERHADAP PRESTASI BELAJAR SISWA PADA SMP NEGERI 14 KOTA BANDA ACEH - Sukmawati .; Yusrizal .; Niswanto2 . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Student achievement is highly dependent on the involvement of teachers in learning, good competence and high motivation. This study aims to determine whether there is influence between competence and motivation of teachers to student achievement SMP Negeri 14 Banda Aceh. This study uses a quantitative approach with descriptive methods. As the population used in this study was the teacher in charge of SMP Negeri 14 Banda Aceh, while the sampled many as 36 people. Methods of data analysis used in this study were multiple linear regression. The results based on multiple linear regression equation obtained Y = 2.227 + 0,172X1 + 0,264X2. The results showed that in partial competence of teachers have a significant effect on student achievement SMP Negeri 14 Banda Aceh with values obtained regression coefficient of 0.172, partially work motivation of teachers also have a significant influence on student achievement SMP Negeri 14, Kota Banda Aceh with values obtained regression coefficient of 0264 and the results of simultaneous testing also showed that the variables of the competence and motivation of teachers have a significant influence on student achievement SMP Negeri 14 Banda Aceh with values obtained Ftest 15.815, while the Ftable at a significance level α = 5% amounted to 3,284. This is shown, based on the calculation of F statistical test show that F count F table, with a probability level of 0.000, thus the hypothesis proposed is accepted.Keywords: competence, teacher work motivation and achievement